A role for preparatory midfrontal theta in autism as revealed by a high executive load brain–computer interface reverse spelling task - Camila Dias; Teresa Sousa; Aniana Cruz; Diana Costa; Susana Mouga; João Castelhano; Gabriel Pires; Miguel Castelo-Branco (Scientific Reports)
Abstract Midfrontal theta oscillations have been linked to executive function, yet their role in autism—where this function is often compromised—remains unclear. We hypothesized that preparatory increases in theta power may help normalize performance in autism. To test this, we used a challenging interactive executive function task designed to impose a high working memory load and require constant error monitoring. An electroencephalogram (EEG)-based brain–computer interface (BCI) was used to maximize cognitive load and engagement. Neural activity from autistic and non-autistic adults was compared while participants were asked to mentally reverse pseudowords (engaging working memory) and write them using the BCI, which provided real-time performance feedback (maximizing error monitoring). The study focused on theta power modulation during the preparatory (pre-response) and feedback (post-response) periods but also explored the role of posterior alpha oscillations. Results showed similar task performance between groups, but distinct recruitment of brain resources, particularly during the preparatory period. The finding of an increased preparatory theta in autism favors the hypothesis of compensatory recruitment of cognitive control and attentional mechanisms to achieve accurate results.